2001
DOI: 10.1081/prg-100104172
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Diagnoses of Preeclampsia

Abstract: Scientific and clinical research groups are studying different preeclamptic groups as a result of using different definitions of this condition. As comparison of results among studies is fundamental to the correct elucidation of knowledge about preeclampsia, standardization of the classification and diagnostic criteria of the hypertensive disorders of pregnancy should be a major priority of societies devoted to the study of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Possible differences are that in the PIERS study pre-eclampsia was considered in the absence of proteinuria, if hypertension and hyperuricemia or HELLP syndrome were present. Indeed it is likely that the heterogeneity amongst these and many previous studies is a facet of the different diagnostic criteria employed in the definition of pre-eclampsia, which originates from incomplete comprehension of its pathophysiology and likely diverse aetiology[24]. Nevertheless in the PIERS study an increased odds of adverse outcomes was observed when 3 to 4+ dipstick proteinuria was detected [17].…”
Section: Discussionmentioning
confidence: 99%
“…Possible differences are that in the PIERS study pre-eclampsia was considered in the absence of proteinuria, if hypertension and hyperuricemia or HELLP syndrome were present. Indeed it is likely that the heterogeneity amongst these and many previous studies is a facet of the different diagnostic criteria employed in the definition of pre-eclampsia, which originates from incomplete comprehension of its pathophysiology and likely diverse aetiology[24]. Nevertheless in the PIERS study an increased odds of adverse outcomes was observed when 3 to 4+ dipstick proteinuria was detected [17].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of pre-eclampsia may vary between studies. 12 We used the definition of pre-eclampsia in Norway (blood pressure >140/90 mmHg and proteinuria; ‡ 1+ on dipstick) and thereby also in the Medical Birth Registry of Norway. This definition is widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta is weighed immediately after delivery, fresh with membranes and umbilical cord attached. Using all placentas, z-scores of placental weight were calculated according to placental weight for gestational age and offspring sex, 12 and divided into ten categories (deciles) with equal numbers in each, with category one as the smallest and category ten as the largest placentas.…”
Section: Methodsmentioning
confidence: 99%
“…The threshold for abnormal protein excretion is increased to 300 mg per day, or 30 mg/mmol creatinine. 19 This threshold is an all or none categorization of renal involvement as there has been no evidence that the foetal or maternal outcomes are directly related to the degree of proteinuria. In everyday clinical practice the spot test has the ease of collection but requires local validation; in some centres the protein creatinine ratio is still questioned in terms of reliability.…”
Section: Renal Involvement In Preeclampsiamentioning
confidence: 99%
“…Much work has been done to validate a spot urine test of protein : creatinine ratio to establish a firm diagnosis of proteinuria 18 compared with the clinical ‘gold standard’ of a 24 h urine collection for protein assessment. The threshold for abnormal protein excretion is increased to 300 mg per day, or 30 mg/mmol creatinine 19 . This threshold is an all or none categorization of renal involvement as there has been no evidence that the foetal or maternal outcomes are directly related to the degree of proteinuria.…”
Section: Renal Involvement In Preeclampsiamentioning
confidence: 99%